Study of the cytotoxic effect of secretory phospholipase A2 of Vipera nikolskii venom on the model of HeLа and ECV340 cell lines - M. A. Solovyeva; L. V. Galebskaya; M. A. Galkin; O. S. Shemchuk; V. V. Sharoyko; L. V. Vasina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Snake venoms have long been the subject of research in order to obtain new antitumor compounds. Snake secretory phospholipase A2 has cytotoxic properties that are realized through different mechanisms depending on the enzyme structure and cell type. HeLa and ECV340 cells were used as a model to evaluate the toxic effect of sPLA2 in the venom of V. nikolskii with and without sPLA2 inhibition. Varespladib was used as an inhibitor of sPLA2. In order to understand the mechanism of the toxic effect of sPLA2, the enzyme was activated by adding an emulsion of phospholipids, bovine serum albumin, and Ca2+ to the samples. The results indicate that the cytotoxic effect of sPLA2 on ECV 340 cells is associated with the catalytic activity of the enzyme; the weak cytotoxic effect of the venom on HeLa cells was preserved upon enzyme activation.Thus, we have proposed a methodological approach that allows to evaluate the toxic effect of sPLA2, which has enzymatic activity, in the whole venom of V. nikolskii in relation to various cell lines.